Analysis of visual signs found in vaseline advertisements - Listyawati , Desak Ayu Chandra; Santika , I Dewa Ayu Devi Maharani; Suastini, Ni Wayan (Institut Pariwisata dan Bisnis Internasional, 2022)
In general, the visual signs have meaning to deliver the messages about the product or service that is advertised to society. This study aims to find out the visual signs and analyze the meanings in Vaseline brand advertisements. To collect the data this study used observation methods. The source of the data was taken from www.vaseline.com website in the form of six body lotion products with various variants. In analyzing the data this study used theory from Saussure (1983: 67) to find out the visual signs in the advertisement, the second theory from Barthes (1961-1974) to analyze the meanings, and the last theory from Cerrato (2012) to analyze the color meaning. The results of this study there are several objects such as pictures and color choices that are found in Vaseline advertisements, also each sign has denotative and connotative meanings which are interconnected.